(untitled) (International Conference on Computers in Education, 2013)
In this paper, we describe the development of a management game, My-Pet-Shop, to support incidental learning for English vocabulary. The design rationale of the system lies in the fact that vocabulary learning should learn from meaningful context rather than abstract description. In addition, a management game could help students regulate their learning in a joyful way. Based on the two rationales, we develop the My-Pet-Shop, which consists of three components, including self-representation, self-management, and social interaction. In addition to the introduction of the three components, their underlying thoughts are also described. In the near future, the system usability and its influences on student learning would be conducted.